6-Substituted amiloride derivatives as inhibitors of the urokinase-type plasminogen activator for use in metastatic disease. Issue 24 (15th December 2019) - Buckley, Benjamin J.; Majed, Hiwa; Aboelela, Ashraf; Minaei, Elahe; Jiang, Longguang; Fildes, Karen; Cheung, Chen-Yi; Johnson, Darren; Bachovchin, Daniel; Cook, Gregory M.; Huang, Mingdong; Ranson, Marie; et al.
Graphical abstract: Abstract: The oral K+-sparing diuretic amiloride shows anti-cancer side-activities in multiple rodent models. These effects appear to arise, at least in part, through moderate inhibition of the urokinase-type plasminogen activator (uPA, Ki  = 2.4 µM), a pro-metastatic trypsin-like serine protease that is upregulated in many aggressive solid malignancies. In applying the selective optimization of side-activity (SOSA) approach, a focused library of twenty two 6-substituted amiloride derivatives were prepared, with multiple examples displaying uPA inhibitory potencies in the nM range. X-ray co-crystal structures revealed that the potency increases relative to amiloride arise from increased occupancy of uPA's S1β subsite by the appended 6-substituents. Leading compounds were shown to have high selectivity over related trypsin-like serine proteases and no diuretic or anti-kaliuretic effects in rats. Compound 15 showed anti-metastatic effects in a xenografted mouse model of late-stage lung metastasis.